Assisted reproductive technology: prevalence and associated factors in Southern Brazil - Shana Ginar da Silva; Andréa Dâmaso Bertoldi; Mariângela Freitas da Silveira; Marlos Rodrigues Domingues; Kelly R Evenson; Iná Silva dos Santos (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE: To assess the prevalence of successful assisted reproductive technology and to identify the associated factors. METHODS: This population-based birth cohort study was carried out with 4,333 pregnant women expected to deliver in 2015 in the urban area of Pelotas, Southern Brazil. Use of an assisted reproductive technology procedure, type of assisted reproductive technology [in vitro fertilization or intracytoplasmic sperm injection or artificial insemination], number of embryos transferred, success of embryo transfer, number of attempts, and reported reasons for seeking assisted reproductive technology were the main outcomes measured. Use of an assisted reproductive technology procedure was analyzed according to sociodemographic, nutritional, reproductive history, and behavioral characteristics. Unadjusted and adjusted analyses were performed by logistic regression. RESULTS: Among the 4,275 newborns enrolled in the Pelotas 2015 Birth Cohort Study, 18 births (0.4%) were conceived by assisted reproductive technology. Most cases of assisted reproductive technology were by in vitro fertilization (70.6%). All cycles were performed in private clinics under direct out-of-pocket payment. Even after controlling for confounders, maternal age > 35 years, nulliparity and high family monthly income were strongly associated with assisted reproductive technology. CONCLUSIONS: The use of assisted reproductive technology services was reported by only a few women in the Pelotas 2015 Birth Cohort Study. Our study highlights sociodemographic factors associated to assisted reproductive technology procedures. To better understand the patterns and barriers in overall use of assisted reproductive technology services over time, national-level trend studies in assisted reproductive technology treatments and outcomes, as well as studies exploring the characteristics of women who have sought this kind of treatment are needed in low-middle income countries.